UPCYCLING WASTE BELACU FABRICS INTO WOMEN'S READY TO WEAR CLOTHES - Nuraeni, Cucu
In Indonesia the fashion industry continues to grow, various kinds of trends always change every year but this also has a big impact on environmental welfare, increasing human needs and increasing demand for natural resources (SDA). This causes an imbalance between the materials needed and also the increasing needs, not only that the impact caused by the fashion industry is also very large, one of which is the fabric waste that is produced during the clothing production process. Until now, clothing manufacturers as well as designers are trying to reduce clothing production waste by utilizing the remaining used fabrics to be reprocessed into more valuable products. This research uses a qualitative methodology with an exploration process of designing and manufacturing fashion products as well as conducting a survey of the results of research product design to several consumers. This research aims to help reduce problems that occur due to factors in the development of the fashion industry, as well as finding out consumers' interests and interests in recycled designs and clothing. In addition to helping clothing manufacturers, designers and craftsmen to work together in organizing a better lifestyle. good for the environment and makes this a form of new trend and unlimited creativity to produce works that are more varied and also more unique. The fashion waste used in this research is leftover calico fabric, using the upcycle technique (processing without losing its original shape). This technique is quite simple and easier to process, using techniques such as cut off, athering, beading, patchwork, quilting, embroidery. With the process of sorting the calico waste, then the process of bleaching and combining the waste into one sheet of cloth. By using the technique of making drafting patterns, it is sewn to form flat patterns and patterns, using the technique of attaching a pile of fabric and then sewing it together and then adding beads or sequins as decoration. This adds value to the aesthetics of this research product and also clothing that only exists in the world because its manufacture only relies on fabric scraps which are reprocessed into new, more valuable products.